Jobs, Well-Being, and Social Cohesion: Evidence from Value and Perception Surveys - Wietzke, Frank-Borge (World Bank, Washington, D.C., 2013)
Recent events, including the Arab Revolutions and protest movement of unemployed youths in OECD countries, have contributed to the popular sentiment that access to good jobs is an important driver of social cohesion. While economic dimensions of labor market outcomes are relatively well documented, evidence on the link between social cohesion and employment conditions is still surprisingly scarce. This paper, a background report for the WDR 2013 on Jobs, presents descriptive evidence that illustrates possible linkages between labor market outcomes and social cohesion. The findings suggest that, once one passes the threshold from low to lower middle income countries, formal employment emerges as a determinant of a range of outcomes relating to social cohesion, such as membership in social associations or levels of political activism. There are also indications of an increasing association between work and life satisfaction across higher and lower middle income countries. The paper concludes with a discussion of the study's implications for emerging economies whose labor market and social institutions are still in transition.